Multifunction vacuum polarization cell - GUOYOU HUANG (2006)
This invention relates to a semiconductor PN junction battery, which utilizes the polarization action of an electric field in the PN junction between metal plates to generate potential difference between them including: depositing a semiconductor PN junction film between two metal plates with very small distance, the vacuum expansion and reduction of which and the polarization action of the built-in electric field in the PN junction generate potential different to provide electric energy to the load. The battery can work continuously in darkness. Multi-laminated batteries with the same structure can get even greater power.